The Angiotensin II Type 2 Receptor, a Target for Protection and Regeneration of the Peripheral Nervous System? - Aurore Danigo; Amandine Rovini; Flavien Bessaguet; Hichem Bouchenaki; Amandine Bernard; Franck Sturtz; Sylvie Bourthoumieu; Alexis Desmoulière; Laurent Magy; Claire Demiot (Pharmaceuticals, 2021)
Preclinical evidence, accumulated over the past decade, indicates that the angiotensin II type 2 receptor (AT2R) stimulation exerts significant neuroprotective effects in various animal models of neuronal injury, notably in the central nervous system. While the atypical G protein-coupled receptor superfamily nature of AT2R and its related signaling are still under investigation, pharmacological studies have shown that stimulation of AT2R leads to neuritogenesis in vitro and in vivo. In this review, we focus on the potential neuroprotective and neuroregenerative roles of AT2R specifically in the peripheral nervous system (PNS). The first section describes the evidence for AT2R expression in the PNS and highlights current controversies concerning the cellular distribution of the receptor. The second section focuses on AT2R signaling implicated in neuronal survival and in neurite outgrowth. The following sections review the relatively few preclinical studies highlighting the putative neuroprotective and neuroregenerative effects of AT2R stimulation in the context of peripheral neuropathy.